Tinjauan Umum Kekuatan Pembuktian Dokumen Elektronik Berupa Akta Autentik Sebagai Alat Bukti Dalam Persidangan Perdata Secara Elektronik (E-litigasi)* - Rodiah, Siti Aisyatur; Sunarjo, Sunarjo; Shanty, Wika Yudha (University of Merdeka Malang, 2020)
This research focuses on how the power of proof of electronic documents in the form of authentic deeds as evidence in electronic civil proceedings (e-litigation) and how legal interpretations to consider electronic documents in the form of authentic deeds as evidence in electronic civil proceedings (e-litigation). The method used in this research is the normative method. Electronic documents in the form of authentic deeds are valid evidence in civil procedural law if they meet the formal and material requirements stipulated in the provisions of Articles 5 and 6 of the ITE Law, namely if the documents are original, can be accessed, displayed, their integrity is guaranteed, and can be accounted for. However, the value of evidentiary power attached to electronic documents in the form of authentic deeds as evidence does not yet have perfect evidentiary power. Because it still requires specific arrangements with the aim of ensuring legal certainty. Even though it has not been specifically regulated, electronic documentary evidence in the form of authentic deeds is still often used in electronic civil proceedings (e-litigation), in which case the judge cannot reject the case. Therefore, judges can make legal discoveries with interpretation and construction methods by referring to the ITE Law.